Kebijakan Akselerasi Pembangunan Infrastruktur Dalam Memenuhi Hak Konstitusional Warga Negara Wilayah Tertinggal, Terluar dan Terdepan - Jonathan Santandrea; Samuel Samuel; Elvinelly Elvinelly (STAATSRECHT: Indonesian Constitutional Law Journal, 2018)
AbstractGaps between regions and underdevelopment of an area are still issues that must be addressed. Thus, the objectives of social welfare and fulfillment of the constitutional rights of Indonesian citizens can be realized. Because, realizing social welfare is one of the goals of the State of the Republic of Indonesia which is stated in the opening of the 1945 Constitution of the Republic of Indonesia.Indonesia is still experiencing social inequality, as evidenced by the fact that there are still a number of regions in the Unitary State of the Republic of Indonesia that are left behind, outermost, and frontier which are considered to have lower development and welfare indexes than other regions in general. To overcome this problem, the Government in the National Medium Term Development Plan (RPJMN) for the 2015-2019 period prioritizes acceleration of infrastructure development in order to realize equitable national social welfare and development.In its implementation, this plan does look very effective because of real results. However, if seen further, it turns out that it is still far from effective, because it is sad in various regions to be the government's top priority such as in Eastern Indonesia (KTI). Therefore, the accelerated development policy must pay more attention to the economic aspects of society, human resources, facilities and infrastructure, regional financial capacity, accessibility and regional characteristics in order to run effectively.Keywords: Acceleration of Infrastructure Development, Constitutional Rights, Social Welfare Abstrak Kesenjangan antar wilayah dan ketertinggalan suatu daerah masih menjadi isu yang harus diatasi. Sehingga tujuan kesejahteraan sosial dan pemenuhan hak konstitusional warga negara Indonesia dapat terwujud. Karena, mewujudkan kesejahteraan sosial merupakan salah satu tujuan Negarta Republik Indonesia yang tercantum dalam pembukaan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Indonesia masih mengalami kesenjangan sosial, terbukti dengan masih terdapat beberapa wilayah di Negara Kesatuan Republik Indonesia yang tergolong sebagai daerah tertinggal, terluar, dan terdepan yang dianggap mempunyai indeks pembangunan dan kesejahteraan lebih rendah dibandingkan dengan daerah lain pada umumnya. Untuk mengatasi permasalahan tersebut, Pemerintah pada Rencana Pembangunan Jangka Menengah Nasional (RPJMN) Periode 2015-2019 memprioritaskan akselerasi pembangunan infrastruktur dalam rangka mewujudkan kesejahteraan sosial dan pembangunan nasional yang merata. Dalam pelaksanaannya, rencana ini memang terlihat sangat efektif karena hasil yang real. Namun, jika dilihat lebih jauh ternyata masih jauh dari kata efektif, karena mirisnya di berbagai wilayah yang menjadi prioritas utama pemerintah seperti di Kawasan Timur Indonesia (KTI). Oleh karena itu, maka kebijakan akselerasi pembangunan harus lebih memperhatikan aspek-aspek perekonomian masyarakat, sumber daya manusia, sarana dan prasarana, kemampuan keuangan daerah, aksesbilitas dan karakteristik daerah agar dapat berjalan secara efektif.Kata kunci : Akselerasi Pembangunan Infrastruktur, Hak Konstitusional, Kesejahteraan Sosial